Interrelationships between spinal and pelvic angles and hip muscle indices and their implications for workspace design - Bridger, Robert S (Department of Human Biology, 2018)
The shape of the lumbar and thoracic spinal curves in healthy subjects, when standing and when adopting a variety of working positions, was investigated using angular measures. The hypothesis that spinal and pelvic posture is determined by body position was supported. The mechanism by which body position influences spinal and pelvic posture was investigated using angular indices of the lengths of the hip flexors and extensors. The hypothesis that hamstring stretch determines postural adaptation to sitting positions was not supported. A multivariate analysis revealed that an index of iliopsoas length was the best predictor of posterior pelvic tilt in a variety of sitting positions. A supplementary investigation was carried out using data on the range of motion of the pelvis in the different body positions and its relationship to the muscle length indices. The role of the hamstring muscles in sitting posture was clarified. Some electromyographic data is presented to further illustrate the effect of body position on the role of the hip and trunk muscles in posture. A replication of the main findings and an investigation of some of the practical implications of the work were carried out drawing attention to some mechanisms of postural stress, potential problems of increased lumbar lordosis and their cost-effective alleviation through workspace design. The provision of a footrest, for example, was found to have significant effects on lumbar and pelvic angles in standing as well as in sitting. Further research into standing posture in the workplace is indicated by these findings. Some hypotheses for future investigation are presented.